n=4(2n+32)+2(n+9/2)

Simple and best practice solution for n=4(2n+32)+2(n+9/2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for n=4(2n+32)+2(n+9/2) equation:



n=4(2n+32)+2(n+9/2)
We move all terms to the left:
n-(4(2n+32)+2(n+9/2))=0
We add all the numbers together, and all the variables
n-(4(2n+32)+2(+n+9/2))=0
We multiply all the terms by the denominator
n*2))-(4(2n+n+9+32)+2(=0
We add all the numbers together, and all the variables
n*2))-(4(3n+41)+2(=0
We add all the numbers together, and all the variables
n*2))-(4(3n=0
Wy multiply elements
2n^2=0
a = 2; b = 0; c = 0;
Δ = b2-4ac
Δ = 02-4·2·0
Δ = 0
Delta is equal to zero, so there is only one solution to the equation
Stosujemy wzór:
$n=\frac{-b}{2a}=\frac{0}{4}=0$

See similar equations:

| 1.14-3x=0 | | 20x-4=6x | | 4u-5+u=16 | | (-(3)+6)/((3-3)^2-6)=y | | 6m-11=9+1 | | ((-(1)+6)((1-3)^2-6))=y | | Y-1/3x=4x | | 6/80=x/100 | | 4z+16=18 | | ((5-3)^2-6)-(-(5)+6)=y | | (4/5)x=0 | | (9)9-2x=7x | | 21/80=x/100 | | (-(5)+6)-((5-3)^2-6)=y | | 8w+9=0 | | 5r-55=2r+14 | | (-(3)+6)-((5-3)^2-6)=y | | 3x=12+7x | | 15/80=x/100 | | (-(3)+6)+((3-3)^2-6)=y | | (-(1)+6)+((1-3)^2-6)=y | | 7m+19÷2=13 | | 8/13=x/52 | | 14/80=x/100 | | 15-x=2x+16 | | 2.5x+1.9=0.9x | | 21/x+7=7/3 | | 2.36−0.2(x+0.8)=x+0.5(0.4x−1.2) | | 6=3-5(y+2) | | -4t+1=3t=1-7t | | m=7+4/2 | | ((x^2)-36)^1/2=8 |

Equations solver categories